Contingency Leadership and Its Effects on Worker Performance in Ambon City's Ministry of Religious Affairs - Pattimukay, Hengky V.R.; Sahetapy, Petronela (MultiTech Publisher, 2023)
The research explores how the Contingency and Motivation Leadership Model affects Ambon City Ministry of Religious Affairs Office employee performance. This research examines how contingency leadership affects Ambon City Ministry of Religious Affairs Office staff performance. Quantitative data analysis of 32 study participants using regression analysis. In the Ambon City Ministry of Religious Affairs Office employee performance, the partial contingency leadership approach had no meaningful influence. Employee success in the Ambon City Ministry of Religious Affairs Office depends on motivation. The contingency and motivating leadership styles affect Ambon City Ministry of Religious Affairs Office workers' performance.